Penyuluhan Dan Pelatihan Penghitungan Zakat Mal Pada Masyarakat Di Desa Sumberbendo Kecamatan Pare Kabupaten Kediri - M. Hanif Satria Budi; Suwarno (LP3M IAIFA Kediri, 2023)
The aim of this research is to provide counseling and training on the correct application of Zakat Mal to the community through Jam'iyah Muslimat Ranting in Sumberbendo village. This research was conducted using a qualitative approach. Data collection techniques using the method of observation, interviews and documentation. The results of this research are that the community in Sumberbendo village, Pare subdistrict, Kediri district is a community whose economy is classified as advanced, but still lacks knowledge regarding the correct application of Zakat Mal, this is because in general the majority of people in this village are busy workers and rarely have the opportunity to reviewing fiqh again, especially regarding mal zakat. and after this counseling and training process, the community not only receives information, but tends to try to put it into practice; The public has become more active in asking experts about the study material discussed; People have become more confident in paying zakat on their wealth because they have guidance in the form of based knowledge, as well as the circulation of material that has been distributed.